РАЗВИТИЕ РАДИОАСТРОНОМИЧЕСКОГО ЦЕНТРА ДАННЫХ (RADC) НА ПРАО АКЦ ФИАН - Самодуров, В. А.; Китаева, М. А.; Исаев, Е. А.; Ладейщиков, Д. А.; Думский, Д. В.; Пугачев, В. Д.; Зайцев, А. Ю.; Логвиненко, С. В. (Одеські астрономічні публікації, 2011)
The Radio Astronomy Data Center (RADC) are developed at PRAO ASC LPI in last some years. It consists from: a) the database of most important for radio astronomers astronomical catalogs; b) the database of observational data of Pushchino Radio Astronomy Observatory. The database of astronomical catalogs http://astro.prao.ru/db/ contains few tens of most important catalogs for planning radio astronomy observations. Since 2011 a database of astronomical catalogs actively equipped with graphical tools for data visualization and cross-analysis of catalogues between one with other. The observation database http://observations.prao.ru/ is collected observational data from base observatory instruments and radio telescopes. This database provides access to observation instruments and telescopes descriptions, techniques of making data samples per instruments, information about types of observations, observers and dates of observations and so on.